Effect of in-feed administration and withdrawal of tylosin phosphate on antibiotic resistance in enterococci isolated from feedlot steers - Beukers, Alicia G.; Zaheer, Rahat; Cook, Shaun R.; Stanford, Kim; Chaves, Alexandre V.; Ward, Michael P.; McAllister, Tim A. (Frontiers in Microbiology, 2015)
Tylosin phosphate is a macrolide commonly administered to cattle in North America for the control of liver abscesses. This study investigated the effect of in-feed administration of tylosin phosphate to cattle at subtherapeutic levels and its subsequent withdrawal on macrolide resistance using enterococci as an indicator bacterium. Faecal samples were collected from steers that received no antibiotics and steers administered tylosin phosphate (11 ppm) in-feed for 197 d and withdrawn 28 d before slaughter. Enterococcus species isolated from faecal samples were identified through sequencing the groES-EL intergenic spacer region and subject to antimicrobial susceptibility testing, identification of resistance determinants and pulsed-field gel electrophoresis profiling. Tylosin increased (P<0.05) the proportion of eryR and tylR enterococci within the population. Just prior to its removal, the proportion of eryR and tylR resistant enterococci began decreasing and continued to decrease after tylosin was withdrawn from the diet until there was no difference (P > 0.05) between treatments on d 225. This suggests that antibiotic withdrawal prior to slaughter contributes to a reduction in the proportion of macrolide resistant enterococci entering the food chain. Among the 504 enterococci isolates characterised, E. hirae was found to predominate (n=431), followed by E. villorum (n=32), E. faecium (n=21), E. durans (n=7), E. casseliflavus (n=4), E. mundtii (n=4), E. gallinarum (n=3), E. faecalis (n=1), and E. thailandicus (n=1). The diversity of enterococci was greater in steers at arrival than at exit from the feedlot. Erythromycin resistant isolates harboured the erm(B) and/or msrC gene. Similar PFGE profiles of eryR E. hirae n pre- and post-antibiotic treatment suggests the increased abundance of eryR enterococci after administration of tylosin phosphate reflects selection for strains that were within the bovine gastrointestinal tract of cattle at arrival.